Dietary Moutan Cortex Radicis Improves Serum Antioxidant Capacity and Intestinal Immunity and Alters Colonic Microbiota in Weaned Piglets - Bai, Miaomiao; Liu, Hongnan; Wang, Shanshan; Shu, Qingyan; Xu, Kang; Zhou, Jian; Xiong, Xia; Huang, Ruilin; Deng, Jinping; Yin, Yulong; Liu, Zheng'an (Frontiers in Nutrition, 2021)
Background: Moutan cortex radicis (MCR), as a common traditional Chinese medicine, has been widely used as antipyretic, antiseptic and anti-inflammatory agent in China. Objectives: This study aimed to investigate the effects of dietary MCR supplementation on pigs’ antioxidant capacity and intestinal healthy, and to explore whether MCR exerts positive effects via regulating NF-κB signaling pathway and intestinal microbiota. Methods: MCR powder was identified by LC-MS analysis. Selected 32 weaned piglets (21 d of age, 6.37 ± 0.10 kg average BW) were assigned (8 pens/diet, 1 pigs/pen) to four groups and fed with a corn-soybean basal diet supplemented with 0, 2000, 4000 and 8000 mg/kg MCR for 21 d. After the piglets sacrifice, antioxidant indexes, histomorphology examination and inflammatory signaling pathway expression were assessed. 16s RNA sequencing analyzed the effects of MCR on intestinal flora structure of piglets. Results: Supplemental 4000 mg/kg MCR significantly increased (P < 0.05) the ADG, ADFI, total antioxidative capability, colonic SCFA concentrations and the crypt depth in the jejunum but decreased (P < 0.05) the mRNA expression levels of Interferon γ, tumor necrosis factor-α, interleukin-1β, inhibiting kappa B kinase β (IKKβ), inhibiting nuclear factor kappa-B (IκBα) and nuclear factor kappa-B (NF-κB) in the jejunum and ileum. Microbiota sequencing identified the microbial richness indices (Chao1, ACE, and observed species), the relative abundances of Firmicutes and Lactobacillus were increased (P < 0.05), and the relative abundances of Bacteroides, Parabacteroides, unidentified_Lachnospiraceae and Enterococcus were reduced (P < 0.05) by MCR supplemented. Microbial metabolic phenotypes analysis also showed that the richness of aerobic bacteria and facultative anaerobic bacteria, oxidative stress tolerance, and biofilm forming were significantly increased (P < 0.05), and the richness of anaerobic bacteria and pathogenic potential of gut microbiota were reduced (P < 0.05) by MCR treatment. Conclusions: MCR supplementation improved growth performance and serum antioxidant capacity, alleviated intestinal inflammatory by inhibiting IKKβ/IκBα/NF-κB signaling pathway and affecting intestinal microbiota in weaned piglets.